The pacemaker clinic of the 90's : essentials in brady-pacing - Hemel, Norbert M. van; Wittkampf, F. H. M; Ector, H (Kluwer Academic Publishers, 1995)
Since the first pacemaker implantation in October 1958 by Senning and Elmqvist in Sweden, cardiac pacing for bradycardia has become a well-established therapy. The impressive growth of clinical experience and the rapid development of pacemaker devices have greatly contributed to this situation. The electrical therapy appears to be so easy that insertion of the lead and its connection to the pacemaker generator requires little effort, skill or insight. However, after implantation a patient\'s condition seldom remains stable, which requires a flexible pacing program to cover all new cardiac events, and broad insight from clinician and technical colleagues. The Pacemaker Clinic of the 90\'s teaches anatomical and electrophysiological aspects of pacing, supports the prevention of complications, and points to new developments in the field. Apart from classical indications for cardiac pacing, the book discusses the validity of the latest indications, supporting the cardiologist and the associated professional in selecting the appropriate pacing mode and pacemaker follow-up in individual patients. The Pacemaker Clinic of the 90\'s will be a helpful companion for years to come.
Developments in cardiovascular medicine ; Vol. 175
Keywords: Pacemaker, Artificial; kardiologie; kardiostimulátor